The Influence of Political Stability on Foreign Direct Investment in The Gambia. An ARDL Approach to Short-Run and Long-Run Dynamics - Salim Minteh (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2026)
The political landscape in any country plays a significant role in attracting external investors. A stable and violence free polity is a panacea for sustain investment by and large economic development. Gambia, in the past decades have enjoy a stable political atmosphere required for any potential investors. Against this backdrop, this study empirically investigates the role of political stability in attracting foreign direct investment into Gambian’s economy using annual time series data spanning the period from 1999 to 2023 using the bound test approach to cointegration. The cointegration bound test establishes that there is a long-run equilibrium relationship between political stability, Inflation, GDP, Trade and FDI. The result of the Error Correction Model (ECM) is negative and statistically significant, which implies that there exists a long-run association between the independent variables and FDI. The long-run coefficient indicated that Political stability as determined by the Political Stability and Absence of Violence/Terrorism index has a positive and insignificant long-run impact on FDI. Additionally, trade openness as the ratio of total trade to GDP has a negative statistically significant impact on FDI at 10% level. Both the inflation (measured by the change in consumer price index on an annual basis) and GDP (annual growth in real gross domestic product) growth are indicated to have a negative but statistically insignificant impact on FDI in the long run. The study suggests that the Government of The Gambia should reinforce its strategic plans of foreign direct investment (FDI) in an attempt to improve the economic stability of the country. The results have shown that a greater level of political stability will help in enhancing governance and reliability of regulation contributing to a better forecasted investment climate.